2022
DOI: 10.34172/apb.2023.029
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics for the Management of Oral Mucositis: An Interpretive Review of Current Evidence

Abstract: Mucositis is one of the major side effects of anti-cancer therapies. Mucositis may lead to other abnormalities such as depression, infection, and pain, especially in young patients. Although there is no specific treatment for mucositis, several pharmacological and non-pharmacological options are available to prevent its complications. Probiotics have been recently considered as a preferable protocol to lessen the complications of chemotherapy, including mucositis. Probiotics could affect mucositis by anti-infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Hong et al also demonstrated that OM severity is associated with 5-FU [134]. Modification of oral microbiome is a promising preventive treatment for OM [135,136]. Palifermin, which is the only pharmacological agent approved by the FDA to treat OM, is a recombinant human keratinocyte growth factor (KGF) that targets the KGF receptor to enhance the differentiation and maturation of epithelial cells [132,137].…”
Section: Microbiota and Treatment Outcomes Of Osccmentioning
confidence: 99%
“…Hong et al also demonstrated that OM severity is associated with 5-FU [134]. Modification of oral microbiome is a promising preventive treatment for OM [135,136]. Palifermin, which is the only pharmacological agent approved by the FDA to treat OM, is a recombinant human keratinocyte growth factor (KGF) that targets the KGF receptor to enhance the differentiation and maturation of epithelial cells [132,137].…”
Section: Microbiota and Treatment Outcomes Of Osccmentioning
confidence: 99%